Strategy for the development of digital competence in the national education system of Ukrainian socety - Batyuk, Liliya; Zhernovnykova, Oksana (Journal of Education, Health and Sport, 2018)
The article examines the issue of the strategy for the development of digital competence in the national education system of Ukrainian society under the influence of intensive development of ICT and in the context of practical recommendations provided by UNESCO regarding the structure of ICT competence of teachers. It was determined that there is no uniform policy of ICT education transformation in public institutions of Ukraine and there are no ICT standards - competences of participants in the educational process. The conceptual vision of informatization of the national education system of Ukraine is described, in the context of strengthening the role of digital competences and technologies. A comparative analysis of the large-scale informatization of the global education system, which led to the emergence of new methods and forms of education, was carried out. It is emphasized that the national education system of Ukraine is slowly introducing new methods and forms of education, which leads to a decrease in the competitiveness of Ukrainian education in the globalized educational space, and as a result leads to a decrease in the country's competitiveness in socio-economic and scientific and technical progress as a whole.